PENERAPAN VIRTUAL LABORATORY DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENDUKUNG PROSES PEMBELAJARAN KIMIA - Iga Haryanti; Yenni Kurniawati; Faisal Hariman Lubis (Journal of Chemistry Education and Integration, 2023)
The implementation of Virtual Laboratory in learning is a 21st century media that is expected to be able to help students master abstract and arithmetic chemistry material. Supported by the PBL learning model, this media is expected to be able to develop students' skills to become independent learners through solving the problems given, so that it is expected to improve student learning outcomes. The research was conducted using a quasi-experimental design with a pretest and posttest design, in order to determine the effect of applying the PBL learning model using virtual laboratory media on students' chemistry learning outcomes. The test instrument supported by observation was analyzed for differences in effect using the t-test. The results showed the significant difference in student learning outcomes, at a significant level of 5% which indicated the influence of virtual laboratory media on the application of the PBL learning model on students' chemistry learning outcomes in the matter of reaction rates, with an effect coefficient of 7.8%.Keywords : Problem Based Learning, Virtual Chemistry Laboratory, Reaction Rate